THE EFFECT OF EUCALYPTUS OIL INHALATION THERAPY ON CHILDREN WITH BRONCHOPNEUMONIA IN THE PEDIATRIC WARD OF GRAHA HERMINE HOSPITAL BATAM CITY - Wulan Pramadhani; Nursasha Izati Pramadhani; Elvi Murniasih; Sorta Tambun (LPPM Universitas dr. Soebandi, 2026)
Bronchopneumonia is one of the leading causes of lower respiratory tract infections in children and is commonly associated with ineffective airway clearance resulting from excessive accumulation of thick airway secretions. Complementary nursing interventions, such as warm steam inhalation with eucalyptus oil, have been proposed to facilitate mucus clearance and improve respiratory function. Objective: To describe the nursing care of a child with bronchopneumonia through the implementation of complementary warm steam inhalation with eucalyptus oil to improve airway clearance. Methods: This study employed a descriptive case study design using a comprehensive nursing care approach. The participant was a 2-year-6-month-old child diagnosed with suspected bronchopneumonia and hospitalized in the pediatric ward of Graha Hermine Hospital, Batam City. Nursing interventions were developed according to the Indonesian Nursing Intervention Standards (SIKI). Complementary warm steam inhalation with three drops of eucalyptus oil added to warm, non-boiling water was administered once daily for three consecutive days (7–9 August 2024) for 15–20 minutes before routine pharmacological treatment. Clinical outcomes were evaluated using the Indonesian Nursing Outcomes Standards (SLKI) based on respiratory rate, sputum production, and adventitious breath sounds. Results: At baseline, the patient presented with shortness of breath, productive cough with thick yellow sputum, a respiratory rate of 32 breaths/min, and bilateral rhonchi on auscultation. Progressive clinical improvement was observed throughout the intervention period. By the third day, sputum production had markedly decreased, rhonchi were minimal to absent, cough effectiveness had improved, and respiratory rate decreased from 37 to 30 breaths/min after the intervention, indicating improved airway clearance. Conclusion: In this case, complementary warm steam inhalation with eucalyptus oil, administered alongside standard medical treatment, was associated with improved airway clearance, as demonstrated by reduced sputum production, diminished adventitious breath sounds, and gradual normalization of respiratory rate. Further studies with larger sample sizes and controlled study designs are needed to confirm the effectiveness and safety of this complementary nursing intervention in pediatric patients with bronchopneumonia.